Magnetic catalysts based on Iron Oxides: Synthesis, Properties and Applications (2018)
This review focuses on the magnetic properties, structure, synthesis and application as catalysts of magnetic nanoparticles of iron oxides. In recent years there have been many advances in its synthesis, control of size and shape, which highlights methods such as co-precipitation, microemulsion, hydrothermal and solvothermal synthesis, among many others. But because the nanoparticles of iron oxides are easily oxidizable by the environment and by acidic means, it is necessary to coat them or protect them with non-magnetic materials that in many cases also function as functionalizing substances to which the phase is attached active Thus, the range of possibilities for protective substances and compounds, such as inorganic oxides, polymers and metals, is broad, as are the techniques for their functionalization. Magnetic nanoparticles, once functionalized, can be used as building blocks for the manufacture of a wide variety of catalytic systems, and in this work we will briefly review some of these systems and their application in different processes such as Organic Synthesis reactions, photocatalysis and elimination of metals and other substances in wastewater, to name a few examples. Finally, some trends and future perspectives in these research areas will be delineated.